Management of COVID-19 Infected Patients in Pregnancy and Puerperium - Sharma, Basant; Dangal, Ganesh; Khanal, Bandana; Angadi, Siddeshwar (Nepal Journal of Obstetrics and Gynaecology, 2020)
COVID-19 is a pandemic affecting every group of people. Pregnancy itself is a partially immune compromised state, so chance of aggravation of symptom supposed to be more in pregnancy. Prevention is the best way to get away from this disease. Good hygiene, supportive care and possible mechanical ventilation for severe case are required. There is no proven role of antibiotic, antiretroviral and steroids. There is no proven vertical transmission. Baby has to be kept in isolation and breast milk can be expressed and given to newborn. Keywords: COVID-19, pandemic, pregnancy.